Kompetensi Profesionalisme Guru Di Bidang Bio- Entrepreneurship Untuk Meningkatkan Kesejahteraan Guru: Literatur Review - Octaviani Fajrin; Franciska Livia Pangemanan; Miftaningtyas Febriani; Eko Retno Mulyaningrum; Reni Rakhmawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
This article aims to educate and provide solutions for biology teachers to become bio-entrepreneurs in order to improve teacher welfare. The research method used is the literature review method to analyze how to become a bio-entrepreneur which can improve teacher welfare. Data was collected by searching for e-journals relevant to this topic via Google Scholar for the last 7 year period from 2017-2024.The results of the analysis from several articles show that: becoming a bio-entrepreneur can improve teacher welfare.